TEACHING MOLECULAR PHYSICS TO 7TH GRADE STUDENTS BASED ON NON-STANDARD TASKS - Karimova Gulchehra Jurabekovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
This article examines the methodological foundations of teaching the molecular physics section to 7th grade students through non-standard tasks. A comparative analysis of standard and non-standard tasks based on Bloom's taxonomy is presented. Practical examples of non-standard tasks on the topics of diffusion, intermolecular forces, and states of matter have been developed. The proposed approach fosters analytical thinking, the ability to connect real-life phenomena with physical laws, and independent inquiry skills in students.